The leopard and the spots : selected extracts from "lessons of my life" - Vansittart, Robert Gilbert (London New York Melbourne : Hutchinson & Co., 1944)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: militarisme; Wereldoorlog 2; Duitsland